Pragmatic Aspects of the Judicial Discourse in the Judgements of Costa Rican Constitutional Courts - Matarrita Arroyo, Mario (2023)
The article examines the way in which two Costa Rican judicial authorities –law courts– behave pragmatically when delivering some of their decisions. With this objective, the text summarizes, in the first place, theoretical contributions about legal language and discourse and then exposes the characteristics of judicial sentences, texts through which a judicial authority presents, to the interested parties and the public in general, the reasons that lead them to make the decision in a case. This theoretical basis serves to, in a second section, study the discourse of some judicial sentences from linguistic pragmatics, fundamentally from Critical Discourse Studies and Speech Act Theory. As a result of this analysis, the text proposes a new classification of substantiation strategies used by the Costa Rican judicial authorities to motivate their decisions.